Ecological and economic significance of swamp vegetation nursery for successful reforestation program: an insight from Bangladesh - Md. Shawkat Islam Sohel; H M Nurul Islam; Md. Amanat Ullah; Kazi Md. Noor Newaz; Malik Fida A Khan; Gopal Chandra Sarker; Md. Sadequr Rahman Bhuiyan (Geology, Ecology, and Landscapes)
There is a growing interest in understanding and establishing forest nurseries in swamp ecosystem areas of Bangladesh. This study aims to evaluate the socio-economic and ecological contribution of swamp small-scale tree nurseries. The result revealed that government and non-government organizations established swamp nurseries in Bangladesh. Swamp nursery producer generates an annual average net profit of USD 4745. Small-scale swamp nursery owners benefited in multiple forms: subsistence, house construction, savings purposes, and, most importantly, expansion of their businesses. However, the ecological aspect of seedling production was not satisfactory because of the lack of facilities such as skilled labor supply, access to high-quality germplasm, technical skills, nursery facilities, etc. In the nurseries observed, only two dominant swamp tree species, locally known as Hijol (Barringtonia acutangular) and Koroch (Pongamia pinnata) seedlings were found. In most cases, those seedlings were morphologically unhealthy, and the root structure was deformed, which was identified as a major problem of reforestation programs in wetland areas. Therefore, to make the reforestation program successful and create livelihoods for the rural poor in the wetland areas, there is an urgent need to develop quality seedlings-based swamp nurseries, which are only possible through proper nursery management techniques.